Is there a link between socio-cultural practices and vulnerability to Rift Valley fever in Baringo County, Kenya? - Mutua, Edna N.; Bukachi, S.A.; Bett, Bernard K.; Estambale, B.B.A.; Nyamongo, I. (International Livestock Research Institute, 2015)
Rift Valley Fever (RVF) is a zoonotic disease that affects domestic ruminants, particularly sheep, cattle and goats. In livestock and humans, RVF is spread through bites from infected aedes and culex mosquitoes. Additional avenues of human infections include contact with infected animal secretions, tissues and aerosols. In Kenya, RVF outbreaks have occurred ten times with the first recorded in 1931 and the last in 2006. During the 2006-2007 outbreak, RVF occurred in Baringo County for the first time. The outbreak was associated with El Nino/Southern Oscillations related climatic anomalies. Through an on-going study on community adaptation to Malaria and RVF, which specifically focuses on how culture influences disease, data on socio-cultural practices in livestock production has been collected through focus group discussions and key informant interviews among the Tugen and Ilchamus communities of Baringo County. Preliminary findings show that both communities largely depend on livestock for their livelihoods. In terms of risk of exposure to RVF, both communities exhibit vulnerability based on their low level of awareness of the disease; consumption of meat from animals that die of diseases and unknown causes; disposal of dead animals; close contact with both healthy and sickly livestock; and management of human febrile illnesses. The study concludes that both communities are vulnerable to RVF and recommends that they should receive targeted awareness creation messages on the occurrence, transmission and prevention of RVF in order to decrease vulnerability to human and livestock infections.